Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4817424
|View full text |Cite
|
Sign up to set email alerts
|

GaAs pillar array-based light emitting diodes fabricated by metal-assisted chemical etching

Abstract: We demonstrate GaAs pillar array-based light emitting diodes (LEDs) with axial p-i-n junctions fabricated using a room-temperature metal-assisted chemical etching (MacEtch) method. Variations in vertical etch rates for all three doping types of GaAs are investigated as a function of etching temperature, oxidant/acid concentration ratio, and dilution of the etching solution. Control over nanopillar morphologies is demonstrated, simply through modification of the etching conditions. Optical emission enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 45 publications
5
92
2
2
Order By: Relevance
“…In this study, the observations regarding the effect of etchant temperature on the etching rate basically agree with the results of a previous study [10]. Although the temperature dependence of the etching rate is not completely understood, it is true that the etching rate is related to the amount of the generated holes, i.e., the temperature-dependent reduction rate of the oxidant.…”
Section: Except With Varyingsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the observations regarding the effect of etchant temperature on the etching rate basically agree with the results of a previous study [10]. Although the temperature dependence of the etching rate is not completely understood, it is true that the etching rate is related to the amount of the generated holes, i.e., the temperature-dependent reduction rate of the oxidant.…”
Section: Except With Varyingsupporting
confidence: 89%
“…Since then, it has been reported that metal-assisted chemical etching can be applied to not only silicon substrates [2][3][4][5] but also other III-V compound semiconductors such as GaAs [6][7][8][9][10] and InP [11][12][13]. For an overview of the metal-assisted chemical etching of silicon, refer to recent reports in the literature [14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…For the carrier transport and redox mechanism that we have proposed in this work, they will have important consequences in the basic understanding and unification of MacEtch processes in general. This can possibly help further studies in the control of porosity57, development of self-assembled lithography with different metals58, design of new process in etching and new etching recipes for multiple compound semiconductors323959.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] In recent years, several research groups have demonstrated the use of MacEtch for the fabrication of micro/nanostructures of various aspect ratios and surface morphologies using both Si and compound semiconductors. 1,[4][5][6][7][8][9] As the technique relies on patterning of a thin noble metallic catalyst layer, which sinks down and engraves into the semiconductor during etching, the semiconductor structures formed using MacEtch are exactly complementary to the metal patterns. Therefore, metal mesh patterns produce vertical pillars 4,[8][9][10] and discrete metal particles yield cylindrical holes.…”
Section: Photonic Crystal Membrane Reflectors By Magnetic Field-guidementioning
confidence: 99%
“…1,[4][5][6][7][8][9] As the technique relies on patterning of a thin noble metallic catalyst layer, which sinks down and engraves into the semiconductor during etching, the semiconductor structures formed using MacEtch are exactly complementary to the metal patterns. Therefore, metal mesh patterns produce vertical pillars 4,[8][9][10] and discrete metal particles yield cylindrical holes. 11 While vertical nanopillar arrays fabricated using MacEtch have been shown for energy harvesting 3,12 and light emitting diode (LED) 9 applications, devices relying on MacEtched nanohole arrays have been more elusive.…”
Section: Photonic Crystal Membrane Reflectors By Magnetic Field-guidementioning
confidence: 99%